Exploring the Design Space for Energy-Harvesting Situated Displays - Grosse-Puppendahl, Tobias; Hodges, Steve; Chen, Nicholas; Helmes, John; Taylor, Stuart; Scott, James; Fromm, Josh; Sweeney, David (UIST '16: Proceedings of the 29th annual ACM symposium on user interface software and technology, 2016)
We explore the design space of energy-neutral situated displays, which give physical presence to digital information. We investigate three central dimensions: energy sources, display technologies, and wireless communications. Based on the power implications from our analysis, we present a thin, wireless, photovoltaic-powered display that is quick and easy to deploy and capable of indefinite operation in indoor lighting conditions. The display uses a low-resolution e-paper architecture, which is 35 times more energy-efficient than smaller-sized high-resolution displays. We present a detailed analysis on power consumption, photovoltaic energy harvesting performance, and a detailed comparison to other display-driving architectures. Depending on the ambient lighting, the display can trigger an update every 1 - 25 minutes and communicate to a PC or smartphone via Bluetooth Low-Energy.